Synaptic plasticity and learning behavior in transparent tungsten oxide-based memristors. (5th September 2017) - Qu, Bo; Du, Haiwei; Wan, Tao; Lin, Xi; Younis, Adnan; Chu, Dewei
Abstract: In this study, by introducing reflex process into the precursor preparation and inkjet printing for high-quality top electrode deposition, we produced a solution-processed tungsten oxide based memristor, which not only overcomes the technical challenges in previous reports but also leads to an important step toward the development of high-performance memristor at low cost and ambient pressure. Various characteristics of synaptic plasticity and learning behaviors have been effectively demonstrated in the stacked device of Ag/WO3 /FTO including short-term plasticity (STP) and long-term plasticity (LTP). A detailed investigation of short-term plasticity to long-term plasticity transition was given by changing the pulse number and strength. The memristive behavior in this work can be attributed to the formation/dissolution of Ag percolation paths between two electrodes. With regard to these promising features, the developed memristor may have great potential applications for bio-inspired neuromorphic devices. Graphical abstract: Highlights: Tungsten oxide based transparent memristor devices were fabricated by using the sol-gel method. The developed oxide precursor showed excellent stability over a couple of months which is superior to previous reports With the structure of Ag/WO3 /FTO, the prepared memristive cells demonstrated bipolar resistive switching behaviors. Synaptic plasticity was mimicked in the device by controlling different pulse number, amplitude and intervals. The formation/dissolution of the metallic silver percolation was demonstrated to be responsible for device operational mechanism.